Revolution in Military Affairs: Strategi Menghadapi Strategic Disadvantage Singapura - Triantama, Febry; Pangestu, Yoga (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2020)
The Singapore government since 2000 has stated their goals to have a strong and capable Singapore Armed Forces (SAF). The urgency of having a strong and capable SAF cannot be separated from the multidimensional threats that Singapore has to deal with. China's growing military capability coupled with increased aggressiveness in the South China Sea and relations with two conflicting neighbors are examples of traditional threats facing Singapore. Non-traditional threats, especially terrorism, also haunt Singapore. This article argues that the Revolution in Military Affairs implemented by Singapore is the mitigation of such strategic disadvantage. Through the implementation of the Revolution in Military Affairs which was marked by the acquisition of advanced weaponry technology and followed by changes in military doctrine and organizational adaptation, the SAF has already been transformed into a powerful military in the region.